Pengaruh Kualitas Produk, Harga, Lokasi Dan Promosi Terhadap Keputusan Pembelian (Studi Kasus PadaToko Prabujaya Malang) - Fandi Agub Harnady; Budi Wahono; Siti Asiyah (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract The purpose and function of this research is to find out how the purchasing decisions of a consumer at the Prabujaya Shop Malang by using product quality, price, location and promotion as predictor variables. This type of research is included in the explanatory research with a quantitative approach using the SPSS statistical program. Then the data used are primary data. Based on the data on the number of visitors at the shop, there were 2100 visitors. Then, using non-probability sampling techniques and incidental sampling, the researcher finally got a sample of 100. And from the results of data processing, it was concluded that product quality, price, location and promotion simultaneously had a significant effect on purchasing decisions. Meanwhile, individually, only the variables of product quality and price have an effect. For location and no promotions. Keyword: Product Quality, Price, Location, Promotion, Buying Decision